Trans-Catheter Palliation in Tetralogy of Fallot Patients: Complications & Challenges - Farhan, Muhammad Asad; Sadiq, Nadeem; Sana, Ayesha; Azizullah; Ara, Andaleeb (Pakistan Armed Forces Medical Journal, 2023)
Objective: To identify the complications of Transcatheter palliation in Tetralogy of Fallot patients.Study Design: Analytical Cross-sectional study.Place and Duration of Study: Paediatric Cardiology Department, AFIC/NIHD, Rawalpindi Pakistan, from Jul to Dec 2022.Methodology: This Analytical Cross-sectional study was conducted in n=54 patients of Tetralogy of Fallot (TOF) who underwent Transcatheter palliation procedure. Cases were selected by using non-probability consecutive sampling. Patients with isolated pulmonary stenosis, complex congenital heart and Tetralogy of Fallot with pulmonary atresia were excluded from the study. Data was entered and analyzed by using SPSS version-24:00. In descriptive statistics, Mean±SD were calculated for continuous variables while frequency (%) for categorical variables. To find out the association between categorical variables, Chi-square test was used. p-value of